Exploration and characterization of a novel cocrystal hydrate consisting of captopril, an amino acid-derived drug. Issue 17 (31st March 2023) - Haku, Ryotaro; Takatori, Kazuhiko; Suzuki, Naoto; Ono, Makoto; Titapiwatanakun, Varin; Fukami, Toshiro
Abstract : We found a novel cocrystal consisting of captopril, which is an amino acid-derived drug having a thiol group, and l -proline by using nano-spot-screening with LF-Raman. This cocrystal hydrate showed high hygroscopicity resulted from changes in intermolecular interactions. Abstract : Cocrystallization is a crystallization technique for drugs that are difficult to crystallize as single components. In this study, we found a novel cocrystal hydrate consisting of captopril (CPL), which is an amino acid-derived drug and has a thiol group, and l -proline (LPR), although a CPL–LPR cocrystal anhydrate has been previously reported. Nano-spot screening elucidated a new LF Raman spectrum for the combination of CPL and LPR due to the formation of a crystalline complex. Single crystal X-ray diffraction analysis revealed that this crystalline complex was a cocrystal hydrate with a stoichiometric ratio of 1 : 1 : 1 CPL : LPR : H2 O in an asymmetric unit. Notably, the CPL–LPR cocrystal hydrate showed high hygroscopicity, and the degradation product of CPL upon a storage stability test could have resulted from the changes in the intermolecular interactions and the location of the water molecules involved in the thiolate formation in the crystal structure. The storage stability tests highlighted a higher amount of CPL degradation product in the CPL–LPR cocrystal hydrate than in the CPL crystal, potentially due to i) increased hygroscopicity, ii) decreased intermolecular interactions that contribute to CPL stabilization and iii) increased reactivity by water molecules for the crystal structure of the CPL–LPR cocrystal hydrate. Therefore, it is suggested to select a coformer with few OH groups involved in the interaction with water or low hygroscopicity to optimize the stable cocrystals of drugs.